Endoplasmic reticulum, protein synthesis and translocation machinery - Nicchitta, Christopher (Henry Stewart Talks, 2007)
Protein sorting in the eukaryotic cell, The discovery of the secretory pathway, Overview discussion of the structure/function of the endoplasmic reticulum, Experimental protocols and landmark experiments leading to the discovery of protein translocation, The signal hypothesis, Signal sequence structure, Signal sequence recognition, SRP receptor and targeting to the ER, Mechanism of protein translocation and the protein translocation channel, Translational regulation on the ER, The unfolded protein response, mRNA partitioning in the cell, Are there alternative pathways for compartmentalizing protein synthesis?
Archived at 2025/05/28